In vivo nose-to-brain delivery of the hydrophilic antiviral ribavirin by microparticle agglomerates. (1st January 2018) - Giuliani, Alessandro; Balducci, Anna Giulia; Zironi, Elisa; Colombo, Gaia; Bortolotti, Fabrizio; Lorenzini, Luca; Galligioni, Viola; Pagliuca, Giampiero; Scagliarini, Alessandra; Calzà, Laura; Sonvico, Fabio
Abstract: Nasal administration has been proposed as a potential approach for the delivery of drugs to the central nervous system. Ribavirin (RBV), an antiviral drug potentially useful to treat viral infections both in humans and animals, has been previously demonstrated to attain several brain compartments after nasal administration. Here, a powder formulation in the form of agglomerates comprising micronized RBV and spray-dried microparticles containing excipients with potential absorption enhancing properties, i.e. mannitol, chitosan, and α-cyclodextrin, was developed for nasal insufflation. The agglomerates were characterized for particle size, agglomeration yield, and ex vivo RBV permeation across rabbit nasal mucosa as well as delivery from an animal dry powder insufflator device. Interestingly, permeation enhancers such as chitosan and mannitol showed a lower amount of RBV permeating across the excised nasal tissue, whereas α-cyclodextrin proved to outperform the other formulations and to match the highly soluble micronized RBV powder taken as a reference. In vivo nasal administration to rats of the agglomerates containing α-cyclodextrin showed an overall higher accumulation of RBV in all the brain compartments analyzed as compared with the micronized RBV administered as such without excipient microparticles. Hence, powder agglomerates are a valuable approach to obtain a nasal formulation potentially attaining nose-to-brain delivery of drugs with minimal processing of the APIs and improvement of the technological and biopharmaceutical properties of micronized API and excipients, as they combine optimal flow properties for handling and dosing, suitable particle size for nasal deposition, high surface area for drug dissolution, and penetration enhancing properties from excipients such as cyclodextrins.